PENGARUH PENGELOLAAN PERSEDIAAN BAHAN BAKU TERHADAP EFISIENSI BIAYA PERSEDIAAN DI PT HARMONI MAKMUR SEJAHTERA - Hartono Hartono; Indit Andaresta (Jurnal Logistik Indonesia, 2021)
The purpose of this study is to determine how much the influence of raw material inventory management to the inventory cost efficiency at PT Harmoni Makmur Sejahtera. This study uses quantity research methods by giving questionnaires to 30 respondents, the calculation and data analysis conducted by using SPSS version 25. From the data proccessing, it was found a correlation value of 0.671, thus it can be concluded that there is a strong correlation between the variables of raw material stock management (X) on the efficiency of inventory costs (Y). Result of R square (R2) value of 0.451 or in the amount of 45.1%, therefore it can be said that the raw material inventory control variable has an effect of 45.1% on inventory cost management. The test results show that the t count is 4.793. The t table value, which is the standard, obtained the t table value at a significance level of 0.05, which is 2.480. The analysis results show the value of t count> t table (4.793> 2.480). This means that Ho is rejected and H1 is accepted, or there is a positive and significant influence between Raw Material Inventory Management on Inventory Efficiency.